Legal mechanisms of public management of financial and economic processes - Shkapin, Denys; Burchak, Yaroslav; Melnyk, Serhii; Tartachnyk, Yurii; Bashinsky, Oleksandr; Agarkov, Volodymyr (Edelweiss Applied Science and Technology, 2024)
The article considers the assertion that law and public administration are each an independent system inevitably interconnected in terms of scientific research or in practice. The role and nature of legal mechanisms within the frame of public administration, in particular in management of financial and economic processes, are considered through the lens of public administration transformation from New Public Management to Smart Governance paradigm.